A CLINICAL CASE OF POSTPARTUM SACROILIITIS - Оксана Николаевна Новикова; Вера Владимировна Карсаева; Дина Владимировна Павловская; Ирина Геннадьевна Лукьянова; Татьяна Анатольевна Сапожкова; Евгений Валерьевич Горбунов; Даниил Денисович Лысенко (Мать и дитя в Кузбассе, 2022)
Despite low incidence of pregnancy-induced sacroiliitis, it is associated with significant morbidity and mortality. Sacroiliitis can be particularly difficult to diagnose because its symptoms are non-specific. A clinical case of postpartum sacroiliitis in a 24-year old patient is reported. The patient complained of severe right buttock pain radiating to the right thigh. In addition, the symptoms of systemic inflammatory response syndrome were present. Right-sided sacroiliitis was recognized by magnetic resonance imaging (MRI).